Application of Economy Token to Self-Care of Mental Illness Patients - Saufa Yuthika Syahdiba; Wardah Wardah; Eka Malfasari; Sri Yanti; Bayu Azhar; Ulia Nelma; Aulya Akbar (Indonesian Journal of Global Health Research, 2021)
Self-care deficit is most of problem in psychiatric nursing diagnoses that characterized by decreased ability to perform activities consisting of bathing, dressing, decorating, eating, toileting or personal hygiene independently. One of the efforts that can be done to reduce this problem is behavioral therapy: Token Economy. The purpose of this study was to identify the effect of behavioral therapy: Token Economy on self-care of mental patients with self-care deficits at the Tampan Mental Hospital, Riau Province. This type of research is quantitative with a quasi-experimental design. The sample in this study was 25 people who were patients with self-care deficits that diagnosed by data from Sebayang Ward Tampan Mental Hospital, Riau Province . The sampling technique is accidental sampling. Data was proceeded by computerized univariate and bivariate analysis. Statistical test using Wilcoxon test after the previous normality test. The results showed that there was a decrease in the level of dependence on self-care. The Z value shows the effect of behavioral therapy: token economy after and before the intervention of -4,414. From the results of the statistical test, it was found that the alpha value (p < 0.05), means that there is a significant effect before and after behavioral therapy: the token economy.